Poor haemoglobin-haematocrit agreement in apparently healthy adult population; a cross-sectional study in Cape Coast Metropolis, Ghana - Grace Ali-Baya; Emmanuel Zenile; Bridgette Obuor Aikins; Regina Elorm Amoaning; David Larbi Simpong; Patrick Adu (Heliyon, 2021)
Background: This study estimated total body water (TBW), daily water intake (DWI) and haemoglobin-haematocrit relationship in adults in a tropical environment where active lifestyles could precipitate plasma volume contraction. Methods: This cross-sectional study recruited 170 participants, and was carried out between February 2018 and May 2018 at University of Cape Coast. Semi-structured questionnaires were used to obtain demographic data and DWI. Five ml of venous blood sample was drawn for full blood count, haemoglobin variant determination, serum sodium and potassium levels. TBW was estimated using Chumlea's anthropometric equation. Statistical significance was set at p < 0.05 under two-tail assumption. Results: Whereas 72.3% had low haematocrit, only 22.4% were anaemic per haemoglobin cut-off demonstrating a poor haemoglobin-haematocrit correlation. Also, whereas 30% of participants had low TBW, 22.9% had hypernatraemia, with 97.1% reporting DWI of <3 L. Bland-Altman plot showed that calculated haematocrit (HCT = Hb∗3) underestimated HCT by a factor of 1.788 (p = 0.0314). A scatter-plot showed a trend towards higher haematocrit-haemoglobin deviations as haemoglobin increased. Furthermore, 32.6% of participants with normal haemoglobin levels had low TBW. Moreover, whereas haemoglobin and serum K+ significantly positively correlated to TBW, serum Na+ was inversely related to TBW. Conclusion: The low DWI is suggestive that measuring plasma volume and/or haemoglobin mass may be required to correctly diagnose anaemia.